(untitled) (Journal of Information Technology and Digital World, 2025)
This paper presents a Savvy Stock Framework for Expiry Date Follow-Up based on an ESP32 microcontroller. The framework organizes different products in different sections of a clever rack. One week prior to the product’s expiration, the system notifies the owner of its shelf location. These alerts are displayed on an LCD screen and sent as notifications. The system also monitors inventory levels and issues low-stock alerts to ensure timely restocking. To increase product safety, the shelves are equipped with a smoke and moisture sensor. If the system detects unusual moisture levels or smoke, it instantly alerts the owner and sounds a buzzer alarm to ensure prompt action.